Some Relevant Aspects of the New Public Procurement Law Interview with Dr. Jorge Danós Ordóñez - Espino Layza, María Alejandra (2015)
The present interview discusses about the new Public Procurement Law and some of the more relevant changes occurred in the matter. In that line, focusing the discussion on the management by result new approach of the law, the role of the public official and the inclusion of the Dispute Boards, the interviewee gives us his authorized opinion about the propose of this reform.